GC-MS SCRUTINY OF PHYTOCONSTITUENTS, IN VITRO EVALUATION OF ANTIHYPERGLYCEMIC, ANTIADIPOGENIC ACTIVITIES, AND CYTOTOXIC EFFECT USING 3T3 L1 ADIPOCYTE CELL LINE AND MOLECULAR DOCKING STUDIES OF PREMNA CORYMBOSA - RADHIKA S; SENTHILKUMAR R (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objective: The present study was intended to list out the phytochemical multiples and to investigate the antihyperglycemic effect of Premna corymbosa using in vitro assays and in silico molecular docking methods. Methods: The phytochemical multiples of methanol proportion of P. corymbosa leaves were appraised by Gas Chromatography-Mass Spectrometry (GC-MS) scrutiny to illustrate the attendance of phytochemical composites. Moreover, the in vitro antihyperglycemic, antiadipogenic activities, and cytotoxic effects of the extract were elucidated using a 3T3 L1 adipocyte cell line. Mode of action of phytochemical composites in methanol leaf extract of P. corymbosa was probed by Western blotting with IRS1, IRS2, mTOR, and glucose transporter type 4 (GLUT 4) receptors. At present, to probe the consequence of the aboriginal drugs, it is necessary to perform in silico docking on the diabetic receptor which could be useful for the progress of enhanced formulation for the psychoanalysis of diabetes. Results: The GC-MS scrutiny depicted the being there of thirty-five phytochemical multipart. Amid the thirty-five multipart’s recognized, focal composites were Phytol, acetate (RT-16.78), n-Hexadecanoic acid (RT-18.16), Phytol (RT-19.51), 9,12,15-octadecatrienoic acid (Z,Z,Z) (RT-19.85), octadecanoic acid (RT-20.04), and Bis (2-ethylhexyl) phthalate (RT-23.09). The results of the glucose conception assay, adipocyte differentiation assay, and MTT assay showed potent in vitro antihyperglycemic activity with methanol leaf extract of P. corymbosa in 3T3l1Cell line. The results attained from western blotting revealed good antihyperglycemic activity of P. corymbosa. The in silico molecular docking results illustrated that the selected herbal lead compound is an effective target against the receptors. The compound showed favorable interactions with the amino acid residues thereby substantiating their proven efficacy as an antihyperglycemic compound. Conclusion: The outcome of the current study substantiates the antihyperglycemic prospective of the methanol leaf extract of P. corymbosa on the hyperglycemic causal agents and its activity against diabetes by a molecular approach.